Building a Bilingual Environment: The Role of Hostel Environment Management in Creating an Immersive Arabic Language Ecosystem - Athoillah, M. Asyrof (Al-Qalam Institue, 2025)
This study examines the pivotal role of dormitory environment management in shaping and sustaining an immersive Arabic language environment at the Nurul Jadid Islamic Boarding School. Adopting a case study design with a qualitative approach, the study collected data through in-depth interviews, participatory observations, and document analysis. The data was analyzed using the Miles & Huberman technique, supported by triangulation to ensure the credibility of the findings. The results of the study show that the planning and implementation of structured Arabic language programs, including the teaching of mufradat, barnamij, muhadarah, and muhadatsah, is the primary foundation in stimulating active and sustainable use of Arabic. Dormitory management plays a vital role in aligning these programs with the daily routine of students, transforming the dormitory into a dynamic natural laboratory for language practice. The application of a comprehensive immersion model, which integrates Arabic into all aspects of religious and cultural life, significantly improves the language competence of students and forms strong language habits. The main conclusion confirms that the success of mastering the Arabic language is highly dependent on the creation of a holistic and integrated immersive ecosystem, with the management of the dormitory environment as a fundamental pillar. This research makes a theoretical contribution to second language acquisition and offers a practical model for similar educational institutions.